Compatible effect or competitive effect: An investigation of attraction spatial interdependency. Issue 8 (December 2019) - Zhou, Bo; Yang, Bi; Liu, Yi
This study empirically examines the spatial interdependency of attractions, using a unique database of 75 important attractions in Guangdong (GD) province, China and spatial econometric models. According to the estimation results, compatible effects apply to the samples in GD overall and in eastern GD, while competitive effects apply to the samples in northern GD. To analyze further, this study finds attraction theme matters to the nature of spatial interdependency. There are competitive effects among natural attraction (NA) and man-made attraction (MA) and insignificant compatible effects among cultural attractions. The competitive effects among NAs have a root in the competition for tourists' time budget, and competitive effects among MAs are related to product homogeneity, resulting from the ubiquitous product imitation in MAs in China. This study concludes that to distinctly diversify attraction theme is a critical way to generate a positive spatial interdependency among attractions within a certain geographic area.